Moscow Rules? 'Red' Unionism and 'Class Against Class' in Britain, Canada, and the United States, 1928-1935 - Manley, John (Labour / Le Travail, 2005)
The article analyzes the claims of traditionalist and revisionist historians concerning communism by comparing industrial work of the national socialist parties in Great Britain, the U.S. and Canada in the period 1928-1935. The efforts made by the national parties to strive for leadership of the working class in the workplace are explored. Traditionalist historians are of the opinion that adequate comprehension of communism requires recognition of subordination of each national party to the demands of Moscow, Russia. According to revisionist historians, the national parties enjoyed autonomy in resisting or adapting to the demands of Moscow.
Keywords: Canada; Communism; Comparative studies; GREAT Britain; Labor Unions; SOCIALIST parties; United States; Working class